The brief: Malaysia's obsession with supplements / Dr. Mohd Shahezwan Abd Wahab - Abd Wahab, Mohd Shahezwan (Faculty of Pharmacy, 2023)
Recently, I had the incredible opportunity to be a guest on the esteemed online news programme "The Brief" by Bernama TV. The topic of discussion revolved around Malaysia's burgeoning obsession with supplements. As a passionate researcher in the area, it was an honour to share my insights during this captivating interview. During the interview, we delved deep into the reasons behind Malaysia's growing fascination with supplements. We explored various aspects, including misconceptions about supplements and the influence of the media on consumer behaviour. I had the opportunity to discuss the potential benefits and risks associated with overconsumption of supplements and the importance of informed decision-making.